Experiencing-With Data: Exploring Posthuman Creativity Through Rhizomatic Empathy. (June 2022) - Vagg, Julia
Posthuman theorizations of creativity direct attention to the material, affective, relational happenings as they emerge between networks of more-than-human bodies in interaction. This necessitates a rethinking of how creativity research is conducted, including the kinds of data collected and how they are analyzed. Drawing on two case studies exploring the relationship between empathy and creativity in theater devising workshops, this article outlines how a multimodal research design combined with an empathic approach to diffractive analysis provides the opportunity to look beyond the linguistic and textual to explore multi-sensory worlds and draw out the complexities of emerging affects. Adapting Karen Barad's diffractive analysis, this empathic approach is embodied and involves experiencing-with data to generate new understandings and questions about posthuman creativity. Rather than speaking for others via observation, recognition, and evaluation, this follows Gilles Deleuze' proposition that thinking should involve embodied encounter, which can disrupt thinking through relational becoming.